Body composition and dietary intake of adolescents from public schools in Blumenau (Brazil) Composição corporal e consumo alimentar de adolescentes da rede pública de ensino de Blumenau (Brasil) - Chiarelli G. (2011)
The objective of this study was to characterize the body composition and dietary intake of adolescents from public schools in Blumenau, Santa Catarina. A total of 268 students aged 12 to 16 years were selected by random non-probability sampling. Anthropometric measures including weight, height, waist circumference, and skinfold thickness were collected using pre-established protocols to estimate nutritional status and body composition. Dietary intake was evaluated using a food frequency questionnaire. Descriptive analysis, frequency analysis, and the Student t-test were used (p<0.05). The results showed that 57% of the subjects were eutrophic; of these 38% presented adequate fat percentage. The diet of the adolescents was characterized by high energy intake (>2493.5 kcal), with the distribution of macronutrients being in accordance with current recommendations. However, 84% of the adolescents consumed excess saturated fatty acids (>10%) and 46% consumed excess cholesterol (>300). Comparison of dietary intake between genders showed a significant difference for protein (t=2.234, p<0.026), vitamin C (t=2.128; p<0.034), iron (t=2.654; p<0.008), and calcium (t=2.239; p<0.026). In conclusion, the results indicate the need to better understand and evaluate food intake in adolescents in order to develop intervention strategies.